Preparation method of carbon-carbon heater
Carbon carbon heaters are prepared by vacuum suction filtration using chopped carbon fibers and phenolic resins in polycrystalline silicon ingot heaters, and carbonization, graphitization and vapor deposition treatments, and the poor integrity and service life of existing graphite heaters are solved. The short problem realizes efficient and low-cost carbon-carbon heater preparation, suitable for high-temperature and high-pressure environments.
Patent Information
- Application Number
- CN202411666678.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2024-12-20
AI Technical Summary
The existing polysilicon ingot heaters use graphite heaters to have problems such as poor integrity, large weight, easy to damage, short service life, and high cost of manual weaving and poor uniformity during the preparation of carbon fiber heaters.
The dispersion of chopped carbon fiber was used to vacuum filtration in the mold, and a mixture of phenolic resin and ethanol was added for a second vacuum filtration, and then released and cured to form. Then carbonization, graphitization, vapor deposition and density enhancement and purification were carried out. The carbon-carbon heater was obtained.
It has achieved good uniformity, excellent conductivity and low cost of carbon and carbon heaters. It can be suitable for high-temperature and high-pressure environments, with extended service life and reduced resistivity, and meets the needs of the photovoltaic industry.
Smart Images

Figure CN119161203A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-carbon heaters, and in particular relates to a method for preparing a carbon-carbon heater. Background Art
[0002] At present, polycrystalline silicon wafers in the photovoltaic industry dominate solar cells with their advantages of high production capacity, low energy consumption and low cost. At present, most polycrystalline silicon ingot heaters are still graphite heaters, but as polycrystalline silicon ingot furnaces become larger and larger, the need for graphite heaters is also increasing. Since large-sized graphite products are extremely difficult to form and expensive, polycrystalline silicon manufacturers find it difficult to accept them. Heaters that are usually assembled with multiple graphite plates by screws are usually used on the market, such as the Chinese patent CN 101265607 A that discloses "graphite heaters for polycrystalline silicon ingot processes". This graphite heater has poor integrity, heavy weight, and is easily damaged during transportation, installation and disassembly. Moreover, graphite materials are easily oxidized at high temperatures, and volatilization is serious, resulting in a continuous decrease in the area of its cross section, a sharp increase in current density, and a great change in the electrical and thermal characteristics of the graphite heating element, resulting in a short service life of about 3 to 4 months.
[0003] Carbon / carbon composite materials have the characteristics of low density, small thermal expansion coefficient, ablation resistance, chemical inertness, thermal shock resistance, high dimensional stability, high conductivity, high temperature resistance, and their resistivity decreases with increasing temperature. They are extremely suitable for making heaters for high-temperature thermal fields. Chinese patent CN 109688643 A discloses a carbon-carbon heater and its manufacturing process, the manufacturing method comprising: cutting carbon fiber into short fibers with a length of 30 to 90 mm, opening and combing them into a web to form a thin web, then evenly laying carbon fiber filament bundles of the same specification on the thin web, and compounding the short fibers and carbon fiber filament bundles into a continuous unidirectional cloth by acupuncture; cutting the unidirectional cloth according to the specification, and then stacking the cut unidirectional cloths together in an alternating layer of 0°-90°, or 0°-45°-90°, and compounding them together by acupuncture to form a preform of the plate; then performing resin dipping, carbonization, densification and high-temperature treatment; but the preform needs to be manually woven during the preparation process, which not only has high labor costs, but also is prone to errors, the pores of the carbon fiber are large and uneven, and the obtained carbon-carbon heater has poor overall uniformity, high resistivity and poor electrical conductivity. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a method for preparing a carbon-carbon heater. The carbon-carbon heater prepared by the present invention has good overall uniformity, low resistivity and good electrical conductivity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a carbon-carbon heater, comprising the following steps: The dispersion of the chopped carbon fibers is subjected to a first vacuum filtration in a mold, a mixed solution of phenolic resin and ethanol is added to the mold for a second vacuum filtration, demolding, and curing to obtain a carbon-carbon heater blank; The carbon-carbon heater blank is impregnated with asphalt or phenolic resin and carbonized, and the obtained carbonized blank is graphitized, vapor-deposited densified and purified to obtain a carbon-carbon heater.
[0006] Preferably, the dispersion of the chopped carbon fiber comprises chopped carbon fiber, polyacrylamide, a dispersant and water; the mass ratio of the chopped carbon fiber to water is 1:50 to 1:100; the mass ratio of the chopped carbon fiber to polyacrylamide is 1:2.5×10 -2 ~1:5×10 -2 .
[0007] Preferably, the dispersant is carboxymethyl cellulose, and the mass ratio of the polyacrylamide to the dispersant is 100:1 to 200:1.
[0008] Preferably, the mass ratio of the chopped carbon fibers in the dispersion of the chopped carbon fibers to the phenolic resin in the mixed solution of the phenolic resin and ethanol is 1:100 to 1:500.
[0009] Preferably, the curing temperature is 100-150° C. and the curing time is 3-6 hours.
[0010] Preferably, the carbonization temperature is 600-1200° C., and the insulation time is 10-36 hours.
[0011] Preferably, the impregnation with asphalt or phenolic resin and the carbonization are performed in a cycle, and the impregnation with asphalt or phenolic resin and the carbonization are repeated 2 to 5 times.
[0012] Preferably, the temperature of the graphitization treatment is 1800-2600° C., and the insulation time is 50-80 hours.
[0013] Preferably, the conditions for the vapor deposition densification include: the carbon source gas used for the vapor deposition is methane or propylene, and the flow rate of the carbon source gas is 1-20 m / s. 3 / h; the temperature of vapor deposition is 1000~1200℃, and the time is 100~300h.
[0014] Preferably, the purification treatment comprises: heating to the temperature of the purification treatment and evacuating, and then simultaneously introducing a purification gas and a protective gas to maintain the pressure; the temperature of the purification treatment is 2000-2500°C.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for preparing a carbon-carbon heater, comprising the following steps: subjecting a dispersion of chopped carbon fibers to a first vacuum filtration in a mold, adding a mixture of phenolic resin and ethanol to the mold for a second vacuum filtration, demolding, and curing to obtain a carbon-carbon heater blank; impregnating the carbon-carbon heater blank with asphalt or phenolic resin and carbonizing it, and subjecting the obtained carbonized blank to graphitization, vapor deposition densification, and purification to obtain a carbon-carbon heater.
[0016] The present invention prepares a carbon-carbon heater blank by vacuum filtration, and then impregnates asphalt or phenolic resin, carbonizes, graphitizes, vapor deposits (CVD densification), and purifies to obtain an integrated carbon-carbon heater; the present invention is formed by vacuum filtration, which can avoid manual weaving errors, and the uniformity of the product is better, and the obtained carbon-carbon heater has good electrical conductivity. At the same time, it can be mass-produced, with greater production capacity, saving labor and raw material costs, saving time and effort. The CVD pyrolytic carbon dense coating can protect the internal carbon-carbon material while reducing the surface open porosity of the carbon-carbon heater, reduce the corrosion of the silicon atmosphere, and extend the service life of the heater. The graphitization treatment can increase the graphitization degree of the carbonized blank and further reduce the resistivity of the carbon-carbon heater.
[0017] The preparation method of the present invention has low raw material consumption, low cost, and convenient operation, and the prepared carbon-carbon heater has good integrity, low impurity content, and excellent electrical conductivity and mechanical properties. The data of the embodiment show that the carbon-carbon heater has low resistivity, and its compressive strength and flexural strength are about twice that of commercially available graphite heaters, indicating that the carbon-carbon heater can be applied to higher temperature and high pressure environments (photovoltaic crystal pulling field), and has a longer service life of 10 to 18 months; the total content of metal impurities in the carbon-carbon heater is less than 50ppm, which meets the use requirements of the photovoltaic industry and can effectively avoid product pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 Schematic diagram of the structure of the carbon-to-carbon heater in the embodiment. DETAILED DESCRIPTION
[0020] The present invention provides a method for preparing a carbon-carbon heater, comprising the following steps: The dispersion of the chopped carbon fibers is subjected to a first vacuum filtration in a mold, a mixed solution of phenolic resin and ethanol is added to the mold for a second vacuum filtration, demolding, and curing to obtain a carbon-carbon heater blank; The carbon-carbon heater blank is impregnated with asphalt or phenolic resin and carbonized, and the obtained carbonized blank is graphitized, vapor-deposited densified and purified to obtain a carbon-carbon heater.
[0021] In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.
[0022] The present invention performs a first vacuum filtration on a dispersion of chopped carbon fibers in a mold, adds a mixed solution of phenolic resin and ethanol into the mold for a second vacuum filtration, demoulds, and solidifies to obtain a carbon-carbon heater blank.
[0023] In the present invention, the length of the chopped carbon fiber is preferably 0 to 2 mm, and is not 0, and is more preferably 0.1 to 1 mm. The length of the chopped carbon fiber of the present invention does not cause the fiber length to be too long and the fiber bridging phenomenon to make the obtained carbon-carbon heater have a large porosity and a small density; nor does it cause the fiber length to be too short and the fiber agglomeration phenomenon to make the obtained carbon-carbon heater uneven.
[0024] In the present invention, the dispersion of the chopped carbon fiber preferably comprises chopped carbon fiber, polyacrylamide, a dispersant and water; the mass ratio of the chopped carbon fiber to water is preferably 1:50 to 1:100; the mass ratio of the chopped carbon fiber to polyacrylamide is preferably 1:2.5×10 -2 ~1:5×10 -2 , more preferably 1:4×10 -2 The dispersant is preferably carboxymethyl cellulose (CMC), and the mass ratio of the polyacrylamide to the dispersant is preferably 100:1 to 200:1.
[0025] In the present invention, the polyacrylamide is a suspending agent and a lubricant, which maintains the uniformity of the dispersion and prevents the staple fibers from sticking and agglomerating.
[0026] In the present invention, the method for preparing the dispersion of chopped carbon fibers preferably comprises the following steps: The polyacrylamide and water are first mixed, and then mixed with the chopped carbon fibers and a dispersant to obtain a dispersion of the chopped carbon fibers.
[0027] In the present invention, the temperature of the first mixing is preferably 60°C, and the first mixing and second mixing methods are preferably stirring. The present invention has no special requirements for the stirring speed. After the second mixing, it is preferred to further include standing, and the temperature of the standing is preferably 60°C, and the time is preferably 1-2 hours to ensure that the dispersion is uniform.
[0028] In the present invention, the pressures of the first vacuum filtration and the second vacuum filtration are independently preferably -0.01 MPa to -0.1 MPa.
[0029] In the present invention, the phenolic resin in the mixed solution of phenolic resin and ethanol is preferably a liquid phenolic resin, and the solid content of the liquid phenolic resin is preferably 65-80%, purchased from Shandong Shengquan New Materials Co., Ltd., model: Tr02. The volume ratio of the liquid phenolic resin to ethanol is preferably 1:2-1:4, more preferably 1:3. The mixed solution of the phenolic resin and ethanol has the function of shaping, and the phenolic resin is solidified at low temperature and cracked into carbon at high temperature.
[0030] In the present invention, the mass ratio of the chopped carbon fibers in the dispersion of the chopped carbon fibers to the phenolic resin in the mixed solution of the phenolic resin and ethanol is preferably 1:100 to 1:500.
[0031] In the present invention, the curing temperature is preferably 100-150° C., and the curing time is preferably 3-6 hours.
[0032] After obtaining the carbon-carbon heater blank, the present invention impregnates the carbon-carbon heater blank with asphalt or phenolic resin and carbonizes it, and then performs graphitization, vapor deposition densification and purification on the obtained carbonized blank to obtain the carbon-carbon heater.
[0033] In the present invention, the impregnation is preferably carried out in a vacuum impregnation furnace, the temperature of the vacuum impregnation furnace is preferably 150-220°C, the pressurization pressure is preferably greater than 3MPa, and the holding time is preferably 1-5h, more preferably 2h. The temperature of the vacuum impregnation furnace described in the present invention can reduce the viscosity of the asphalt (or phenolic resin). After the impregnation, it is preferably also included to cool down so that the asphalt (or phenolic resin) hardens. During the impregnation process, the asphalt (or phenolic resin) fills the pores of the carbon-carbon heater blank.
[0034] In the present invention, the carbonization temperature is preferably 600-1200°C, more preferably 1000°C, and the holding time is preferably 10-36h, more preferably 20h. During the carbonization process, the light phase of the asphalt volatilizes, and aromatic substances remain on the heater blank; at the same time, the structure of the carbon blank changes to graphitization.
[0035] In the present invention, the impregnation with asphalt or phenolic resin and carbonization are preferably performed in a cycle, and the number of repetitions of the impregnation with asphalt or phenolic resin and carbonization is preferably 2 to 5 times, more preferably 2 to 3 times. The impregnation with asphalt or phenolic resin and carbonization has the effect of densification, and the density after densification is preferably greater than 1.4 g / cm³.
[0036] In the present invention, the last carbonization preferably includes finishing, and the finishing preferably includes grinding and trimming. The thickness of the carbonized blank after finishing is preferably 8-15 mm.
[0037] In the present invention, the temperature of the graphitization treatment is preferably 1800-2600°C, more preferably 2200°C, 2300°C, 2400°C or 2600°C, and the holding time is preferably 50-80h; the heating rate from room temperature to the temperature of the graphitization treatment is preferably 80-120°C / h, more preferably 100°C / h. The graphitization treatment is preferably carried out in a protective atmosphere, and the protective atmosphere is preferably an argon atmosphere. The graphitization treatment described in the present invention can improve the graphitization degree of the sample (reduce resistivity) and reduce the internal ash content, improve the product purity, and at the same time expose the internal pores to the inner and outer surfaces to the maximum extent, which is conducive to the next step.
[0038] In the present invention, the gas phase deposition densification is preferably chemical vapor deposition, and the conditions of the chemical vapor deposition preferably include: the carbon source gas used for gas phase deposition is preferably methane or propylene, more preferably methane, and the flow rate of the carbon source gas is preferably 1-20m 3 / h, more preferably 5~15m 3 / h, preferably 10m 3 / h; the temperature of vapor deposition is preferably 1000~1200℃, more preferably 1050~1150℃, and more preferably 1150℃; the heating rate to the vapor deposition temperature is preferably 40~80℃ / h, more preferably 50~70℃ / h; the pressure of vapor deposition is preferably 2~10kPa, more preferably 5~8kPa; the time of each vapor deposition is preferably 100~300h, more preferably 150~250h; the number of repetitions of the vapor deposition is preferably 1~3 times. The effect of the vapor deposition in the present invention is carbon densification, and the density of the carbon-carbon heater after carbon densification is preferably greater than 1.6g / cm³.
[0039] In the present invention, the temperature of the purification treatment is preferably 2000-2500°C, more preferably 2300°C, and the purification treatment preferably includes: heating to the purification treatment temperature and evacuating, and then simultaneously introducing a purification gas and a protective gas to maintain the pressure. The evacuation preferably reaches a limit vacuum.
[0040] In the present invention, the vacuum degree of the ultimate vacuum is preferably 2-10 kPa, more preferably 2-5 kPa; the purified gas is preferably Freon or chlorine, and the flow rate is preferably 1-20 m / s. 3 / h, more preferably 5~15m 3 / h, preferably 10m 3 / h; the protective gas is preferably argon, and the flow rate is preferably 1~20m 3 / h, more preferably 5~15m 3 / h, preferably 10m 3 / h; the time for each introduction of purified gas and protective gas is preferably 3 to 10 minutes, more preferably 5 to 7 minutes; the time for each pressure maintenance is preferably 5 to 10 minutes, more preferably 5 to 7 minutes; the vacuuming, introduction of purified gas and protective gas, and pressure maintenance are preferably performed in a cycle, and the number of cycles repeated is preferably 50 to 80 times, more preferably 60 times.
[0041] During the purification process, impurities in the carbon-carbon composite material (such as metal impurities, inorganic matter remaining in asphalt and resin) are decomposed at high temperature, and the purification gas and protective gas flow through the surface of the material to deeply extract and flush the material, so that the impurities are separated from the material and taken away. With the circulation of the mixed gas (purification gas and protective gas) under high temperature conditions, various impurity elements and ash in the carbon-carbon composite material can be separated, thereby obtaining a highly pure carbon-carbon composite material.
[0042] The preparation method of the carbon-carbon heater provided by the present invention consumes less raw materials, is easy to operate, and saves costs. The obtained carbon-carbon heater has good integrity, less impurity content, and excellent electrical conductivity and mechanical properties.
[0043] In order to further illustrate the present invention, the preparation method of the carbon-carbon heater provided by the present invention is described in detail below in combination with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0044] Example 1 1 kg of carbon fiber was cut and the length of the short fiber was 1 mm. Water and polyacrylamide at a temperature of 60 ° C were added to the container, and the short fiber and CMC were added after stirring until they were fully dissolved. The mass ratio of the short fiber to water was 1:50, and the mass ratio of the short fiber to polyacrylamide was 1:4×10 -2 ; The mass ratio of polyacrylamide to CMC is 100:1; the mixed solution is placed in an oven at 60°C for 2 hours.
[0045] The dispersed mixed liquid is evenly poured into the vacuum mold for filtration by vacuum filtration. The liquid phenolic resin is mixed with alcohol in a volume ratio of 1:3, and the prepared solution is poured into the mold again and filtered again. After the filtration, the mold is removed and then cured in an oven at 100°C for 6 hours to obtain a heater blank.
[0046] Put the blank into the vacuum pressure impregnation furnace and impregnate it with asphalt (softening point 150℃). The vacuum impregnation furnace is heated to 220℃. The vacuum pressure difference is used to suck all the impregnation liquid into the furnace containing the blank. Pressurize it to 50kg. After maintaining the pressure for 2h, the excess impregnation liquid is returned. The furnace is cooled down to harden the asphalt. Finally, it is taken out and put into the carbonization furnace for cracking and carbonization. The carbonization temperature is 1000℃ and the carbonization time is 20h. After carbonization, the heater is fine-processed according to the requirements of the drawing. The main processing steps include grinding and trimming. The thickness of the heater after fine processing is 8mm. The impregnation and carbonization are repeated twice.
[0047] The finished samples were graphitized at a temperature of 2200°C, a protective atmosphere of high-purity argon, a holding time of 80 h, and a heating rate of 100°C / h.
[0048] The graphitized sample was placed in a chemical vapor deposition furnace. The carbon source gas used for deposition was methane, and the flow rate of the carbon source gas was 10m 3 / h, the deposition heating rate is 80℃ / h, the deposition temperature is 1100℃, the deposition pressure is 5kPa, and the deposition time is 150h.
[0049] The purification process is as follows: the purification furnace is heated to the purification temperature (2300°C) and the furnace is evacuated to the ultimate vacuum, and then the purification gas (Freon) and the protective gas (high-purity argon) are introduced at the same time, and the ventilation is stopped and the pressure is maintained for purification. The ultimate vacuum is 5kPa, and the flow rate of the purification gas is 10m 3 / h; the flow rate of protective gas is 10m 3 / h; the time for introducing purified gas and protective gas each time is 5 minutes; the time for maintaining pressure each time is 10 minutes, and the number of times of maintaining pressure is 60 times.
[0050] Figure 1 It is a structural schematic diagram of an integrated carbon-carbon heater.
[0051] Example 2 The difference from Example 1 is that the impregnation and carbonization are cycled for three times, the graphitization treatment temperature of the sample is 2400° C., and the remaining steps are the same as in Example 1.
[0052] Example 3 The difference from Example 1 is that the impregnation and carbonization are cycled for 4 times. The graphitization treatment temperature of the sample is 2600° C., and the other steps are the same as those in Example 1.
[0053] The densities of Examples 1 to 3 after impregnation densification and graphitization treatment are 1.49, 1.57, and 1.62 g / cm³, respectively, and the densities after CVD densification are 1.61, 1.67, and 1.72 g / cm³, respectively.
[0054] Example 4 The difference from Example 3 is that the staple length is 0.1 mm, and the remaining steps are the same as Example 3.
[0055] Comparative Example 1 The difference from Example 3 is that the staple length is 4 mm, and the remaining steps are the same as Example 3.
[0056] Example 5 The difference from Example 3 is that the thickness of the heater after fine processing is changed from 8 mm to 15 mm, and the remaining steps are the same as Example 3.
[0057] Test Case (1) The resistivity of conventional graphite heaters on the market (referred to as graphite heaters) and the carbon-carbon heaters prepared in Examples 1 to 5 and Comparative Example 1 were tested by a resistivity tester. The results are shown in the following table: Table 1 Average resistivity results of graphite heater and carbon-carbon heater of Examples 1 to 5 and Comparative Example 1
[0058] The test data show that the resistivity of the integrated carbon-carbon heater of the present invention is significantly lower than that of the graphite heater. The resistivities of the graphite boats in Examples 1 to 3 that have not been purified are 17.9×10 -6 Ω·m、15.3×10 -6 Ω·m、14.1×10 -6 Ω·m, the present invention can adjust the resistivity of the heater by adjusting the preparation process parameters of the heater (purification treatment), further reducing energy consumption and saving production costs. It can be seen from Example 4, Comparative Example 1 and Example 3 that the length of the staple fiber will affect the resistivity. The present invention reduces the resistivity of the carbon-carbon heater by adjusting the length of the staple fiber to 0~2mm. The thickness of the heater in Example 5 is different from that in Example 3. The present invention can adjust the resistivity by adjusting the thickness of the heater.
[0059] (2) Mechanical properties test The mechanical properties of the carbon-carbon heaters prepared in Examples 1 to 3 and conventional graphite heaters on the market are shown in Table 2, wherein the compressive strength and flexural strength are tested using the three-point bending method.
[0060] Table 2 Mechanical properties of heater
[0061] It can be seen from Table 2 that the compressive strength and flexural strength of the carbon-carbon heaters in Examples 1 to 3 of the present invention are approximately twice that of commercially available graphite heaters, which effectively demonstrates that the carbon-carbon heaters can be applied to more demanding working conditions and have a longer service life, which can reach 10 to 18 months at a high temperature of 1500°C.
[0062] (3) Purity test The carbon-carbon heater of Example 1 was subjected to a GDMS (glow discharge mass spectrometry) test, and the metal impurity element content of the purified carbon-carbon heater was as follows: Table 3 Metal impurity elements of carbon-carbon heater in Example 1, unit: ppm
[0063] As can be seen from Table 3, the carbon-carbon heater has high purity and the total content of metal impurities is less than 50ppm, which meets the use requirements of the photovoltaic industry and can effectively avoid product contamination.
[0064] The preparation method of the carbon-carbon heater of the present invention has low cost, and the prepared carbon-carbon heater has good uniformity, high graphitization degree, low resistivity, and strong oxidation resistance, so it can save energy consumption, improve heating efficiency, and reduce heat loss to the carbon-carbon heater itself.
[0065] Although the above-mentioned embodiments have made a detailed description of the present invention, they are only some embodiments of the present invention, rather than all embodiments. People can also obtain other embodiments based on the embodiments of the present invention without creative work, and these embodiments all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-carbon heater, characterized in that: The following steps are involved: The dispersion of the chopped carbon fibers is subjected to a first vacuum filtration in a mold, a mixed solution of phenolic resin and ethanol is added to the mold for a second vacuum filtration, demolding, and curing to obtain a carbon-carbon heater blank; The carbon-carbon heater blank is impregnated with asphalt or phenolic resin and carbonized, and the obtained carbonized blank is graphitized, vapor-deposited densified and purified to obtain a carbon-carbon heater.
2. The preparation method according to claim 1, characterized in that: The chopped carbon fiber dispersion comprises chopped carbon fiber, polyacrylamide, a dispersant and water; the mass ratio of the chopped carbon fiber to water is 1:50 to 1:100; the mass ratio of the chopped carbon fiber to polyacrylamide is 1:2.5×10 -2 ~1:5×10 -2 .
3. The preparation method according to claim 2, characterized in that: The dispersant is carboxymethyl cellulose, and the mass ratio of the polyacrylamide to the dispersant is 100:1-200:
1.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the chopped carbon fibers in the chopped carbon fiber dispersion to the phenolic resin in the mixed solution of the phenolic resin and ethanol is 1:100 to 1:
500.
5. The preparation method according to claim 1 or 4, characterized in that: The curing temperature is 100-150° C. and the curing time is 3-6 hours.
6. The preparation method according to claim 1, characterized in that: The carbonization temperature is 600-1200° C., and the heat preservation time is 10-36 hours.
7. The preparation method according to claim 1, characterized in that: The impregnation with asphalt or phenolic resin and the carbonization are repeated 2 to 5 times.
8. The preparation method according to claim 1, characterized in that: The temperature of the graphitization treatment is 1800-2600° C., and the insulation time is 50-80 hours.
9. The preparation method according to claim 1, characterized in that: The conditions for the gas phase deposition densification include: the carbon source gas used for the gas phase deposition is methane or propylene, and the flow rate of the carbon source gas is 1-20m 3 / h; the temperature of vapor deposition is 1000~1200℃, and the time is 100~300h.
10. The preparation method according to claim 1, characterized in that: The purification process comprises: heating to the purification process temperature and evacuating, and then simultaneously introducing purification gas and protective gas to maintain the pressure; the purification process temperature is 2000-2500°C.
Citation Information
Patent Citations
Graphite heater for polycrystalline silicon casting ingot process
CN101265607A
Carbon-carbon heater and manufacturing process thereof
CN109688643A
High-purity carbon / carbon composite material as well as preparation method and application thereof
CN114804906A
Preparation method of carbon fiber special-shaped body
CN118561617A
Cited By
All-chemical vapor deposition preparation method of carbon-carbon heater with density of 1.6-1.8 g / cm < 3 >
CN120794671A
Carbon / carbon heating device and preparation method thereof
CN121021168A
Carbon / carbon heating device and method for manufacturing the same
CN121021168B
Method for preparing carbon-carbon heater by asphalt impregnation method
CN121342537A
